Conservation in the dark? The information used to support management decisions. Issue 4 (4th August 2009) - Cook, Carly N; Hockings, Marc; Carter, RW (Bill)
Abstract : The management requirements for protected areas are frequently complex and urgent; as a result, managers often need to act quickly and make decisions with limited supporting evidence at their disposal. Despite demands for high‐quality information, it is unclear how much of this evidence conservation practitioners use to assist with their decision making. We investigated the information used to manage protected areas, based on the evidence reported by practitioners when evaluating their management performance. We examined the management of over 1000 protected areas run by two Australian conservation agencies – Parks Victoria and the New South Wales Department of Environment and Climate Change – an unprecedented scope for this type of study. We found that very few conservation practitioners use evidence‐based knowledge to support their management. The evidence used varies with the management issue, reserve type, and reserve size. Around 60% of conservation management decisions rely on experience‐based information, and many practitioners report having insufficient evidence to assess their management decisions. While experience plays an important role in conservation management, the apparent lack of evidence‐based information to support decision making in the reserves has the potential to compromise outcomes and jeopardize the investment made in protected areas for conservation.